Inhibition of mitochondrial pyruvate carrier 1 by lapatinib ditosylate mitigates Alzheimer's-like disease in D-galactose/ovariectomized rats. (November 2021) - Mansour, Heba M.; Fawzy, Hala M.; El-Khatib, Aiman S.; Khattab, Mahmoud M.
Abstract: Mitochondrial, autophagic impairment, excitotoxicity, and also neuroinflammation are implicated in Alzheimer's disease (AD) pathophysiology. We postulated that inhibiting the mitochondrial pyruvate carrier-1 (MPC-1), which inhibits the activation of the mammalian target of rapamycin (mTOR), may ameliorate the neurodegeneration of hippocampal neurons in the rat AD model. To assess this, we used lapatinib ditosylate (LAP), an anti-cancer drug that inhibits MPC-1 through suppression of estrogen-related receptor-alpha (ERR-α), in D-galactose/ovariectomized rats. AD characteristics were developed in ovariectomized (OVX) rats following an 8-week injection of D-galactose (D-gal) (150 mg/kg, i.p.). The human epidermal growth factor receptor-2 (HER-2) inhibitor, LAP (100 mg/kg, p.o.) was daily administered for 3 weeks. LAP protected against D-gal/OVX-induced changes in cortical and hippocampal neurons along with improvement in learning and memory, as affirmed using Morris water maze (MWM) and novel object recognition (NOR) tests. Furthermore, LAP suppressed the hippocampal expression of Aβ1-42, p-tau, HER-2, p-mTOR, GluR-II, TNF-α, P38-MAPK, NOX-1, ERR-α, and MPC-1. Also, LAP treatment leads to activation of the pro-survival PI3K/Akt pathway. As an epilogue, targeting MPC-1 in the D-gal-induced AD in OVX rats resulted in the enhancement of autophagy, and suppression of neuroinflammation and excitotoxicity. Our work proves that alterations in metabolic signaling as a result of inhibiting MPC-1 were anti-inflammatory and neuroprotective in the AD model, revealing that HER-2, MPC-1, and ERR-α may be promising therapeutic targets for AD. Graphical abstract: Graphical abstract displaying the neuroprotective effects of LAP against D-gal/OVX-mediated AD-like pathological changes. ERR-α; estrogen-related receptors alpha, MPC-1; mitochondrial pyruvate carrier 1, LAP; lapatinib ditosylate, α-Kg; alpha-ketoglutaric acid, PI3K; phosphoinositide 3-kinase, Akt; protein kinase B, mTOR; mammalian target of rapamycin, TNF-α; tumor necrosis factor-alpha (Created with Biorender software ®). Image 1 Highlights: Lapatinib ditosylate is an FDA-approved anti-cancer drug. Inhibition of HER-2 by LAP debilitated Aβ1-42 and p-tau. Inhibition of MPC-1 by LAP suppresses neuroinflammation and excitotoxicity. Inhibition of HER-2, MPC-1, and ERR-α by LAP enhance autophagy. LAP may represent a novel candidate for drug repositioning for the treatment of AD.